До питань підготовки суддів із волейболу в регіонах - Медвідь, Михайло; Бичук, Ігор; Колядюк, Юрій; Данилюк, Андрій; Medvid, Mykhailo; Bychuk, Igor; Kolyadyuk, Yurij; Danylyuk, Andrij (Східноєвропейський національний університет імені Лесі Українки, 2019)
Актуальність. Стрімке зростання кваліфікаційних вимог, зміни офіційних правил змагань і підходи до трактування змін у правилах формують необхідність кількісно-якісної конкуренції на етапах підготовки кваліфікованого судді. Питання підготовки суддів із волейболу доцільно розглядати комплексно, проаналізувавши сучасний стан відповідної роботи в регіонах (областях), динаміку зростання майстерності й рівня кваліфікації. Мета дослідження – виявити та проаналізувати кількісно-якісні характеристики рівня підготовленості суддів із волейболу в регіональних федераціях з урахуванням кваліфікації й рівня, рекомендованої для суддівства, ліги. Методи дослідження – аналіз науково-методичної літератури та даних мережі «Інтернет»; контент-аналіз; методи математичної статистики. Результати роботи. У ході проведення дослідження проаналізовано географічне представництво арбітрів і технічних делегатів у змаганнях, що проводяться під егідою Федерації волейболу України. Обґрунтовано проблемні питання підготовки арбітрів у регіонах відповідно до обласної федерації волейболу, рівня змагань (ліги) та категорії арбітрів («Суддя міжнародної категорії з волейболу» – МК, «Суддя національної категорії з волейболу» – НК, «Суддя першої категорії з волейболу» – І). Узагальнено наявні проблеми й перспективи бездіяльності з питань залучення та навчання суддів, що істотно впливатиме на розвиток волейболу в Україні. Висновки. На матеріалах офіційних документів про призначення суддів і технічних делегатів для обслуговування матчів чемпіонату України різного кваліфікаційного рівня виявлено та проаналізовано кількісно-якісні характеристики рівня підготовленості суддів із волейболу відповідно до регіонального представництва з урахуванням кваліфікації й рівня ліги (96 суддів і 40 технічних делегатів). Визначено проблеми та обґрунтовано невідповідність наявних потреб у підготовці суддів для обслуговування матчів різного рівня та результатів роботи в регіональних федераціях із залучення й навчання молодих арбітрів і вдосконалення рівня підготовленості тих, хто вже виконує суддівські обов’язки.Relevance. The rapid growth of qualification requirements, changes in the official rules of competition and approaches to the interpretation of changes in the rules form the need for quantitative and qualitative competition in the stages of training a qualified judge. The issue of volleyball referees training should be considered comprehensively, analyzing the current state of relevant work in the regions, the dynamics of skill growth and skill level. The Objective of the Study is to identify and analyze the quantitative and qualitative characteristics of the level of training of volleyball referees in regional federations, taking into account the qualifications and the level recommended for refereeing, the league. Research Methods: analysis of scientific and methodological literature and data of the Internet; content analysis; methods of mathematical statistics. Results of Work. During the study, the geographical representation of referees and technical delegates in competitions held under the auspices of the Volleyball Federation of Ukraine was analyzed. Problematic issues of training of referees in the regions in accordance with the regional volleyball federation, level of competitions (league) and category of referees («Judge of the international volleyball category» – IC, «Judge of the national volleyball category» – NC, «Judge of the first category of volleyball» – І). The existing problems and prospects of inaction on the involvement and training of referees, which will significantly affect the development of volleyball in Ukraine, are summarized. Conclusions. The materials of official documents on the appointment of referees and technical delegates to serve matches of the Ukrainian championship of different qualifications revealed and analyzed the quantitative and qualitative characteristics of volleyball referees in accordance with the regional representation, taking into account qualifications and league level (96 referees and 40 technical delegates). Problems have been identified and the inconsistency of existing needs in the training of referees for matches of different levels and the results of work in regional federations to attract and train young referees and improve the level of training of those who already serve as referees has been substantiated.
Training of Volleyball Referees in the Regions
Keywords: волейбол; представництво в регіонах; арбітр; суддівство; організація; підготовка; volleyball; representation in regions; referee; refereeing; organization; training